Species diversity and distribution of Spiraea (Rosaceae) in Kazakhstan - ZHANBOTA TURMANOVA; MERUYERT KURMANBAYEVA; GULZHAINA ALPAMYSSOVA; RAIYMBEK ANATOLIY (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Turmanova Z, Kurmanbayeva M, Alpamyssova G, Anatoliy R. 2026. Species diversity and distribution of Spiraea (Rosaceae) in Kazakhstan. Biodiversitas 27 (7): d270721. https://doi.org/10.13057/biodiv/d270721. Spiraea (Rosaceae) is a diverse genus of woody shrubs widely distributed across the temperate northern hemisphere. Still, its taxonomy and distribution in Central Asia remain incompletely resolved due to fragmented data and limited herbarium digitization. Kazakhstan is a key region for understanding the genus, yet comprehensive data-driven assessments are lacking. This study aimed to evaluate the species composition and distribution patterns of the genus Spiraea in Kazakhstan using herbarium evidence and biodiversity occurrence data. Verified herbarium specimens, published floristic sources, and GBIF records were integrated and analyzed through taxonomic standardization using WFO and POWO, occurrence-data cleaning, spatial mapping, and calculation of EOO and AOO metrics. Ten species of Spiraea were confirmed. Analysis of 939 cleaned records showed strong variation in distribution extent, with S. hypericifolia being the most widespread, while S. alpina, S. lasiocarpa, S. tianschanica, and S. chamaedryfolia were primarily recorded in mountainous regions. Estimates of EOO and AOO revealed substantial differences in range size, reflecting variation in recorded spatial extent and data limitations. Geographic gaps, particularly in western and high-mountain areas, highlight persistent sampling biases and the need for targeted surveys and improved herbarium digitization.